Synthesis and characterization of β-RbSc(CrO4)2 - Melnikov, P. [UNESP]; Ferracin, L. C. [UNESP] (Elsevier, 1995)
Synthesis and crystallographic data are reported for the double rubidium-scandium chromate RbSc(CrO4)2. The parameters of the orthorhombic cell are a = 14.836(2) A ̊; b = 5.627(1) A ̊ and c = 8.835(4) A ̊, Z = 4. The compound is closely related to the lamellar double chromates with other alkali metal cations, iron, lanthanides and yttrium offering the advantage of obtaining inorganic materials for electronics. © 1995.
Keywords: Double chromates; Rubidium; Scandium; Synthesis